All-On-Four Concept Literature Review - Isufi, Ramazan; Xhajanka, Edit; Thodhorjani, Anis; Hysenaj, Neada; Lela, Fatmir; Bara, Silvana; Isufi, Renato (International Journal of Membrane Science and Technology, 2023)
The All-on-4 concept is a dental implant technique that provides a solution for patients who have lost or are about to lose all of their teeth in one or both jaws. This concept was developed to simplify the implant process and make it more accessible for individuals with extensive tooth loss. In the review performed in Pubmed and Cochrane Library between 2005 and 2023, Full arch implant-supported prosthesis, 4-implant full arc, osseointegration, inclined implant, total edentulism and different combinations in which some of these keywords were used together were chosen. 100 of the articles achieved from the review were evaluated with respect to the subject we examined. The inclusion criteria for articles were as follows: 1-Articles were related to the all-on-four concept. 2-Abstracts were obtained when the full texts could not be obtained. The All-on-4 concept in dental implantology offers several advantages, making it a popular and effective solution for patients with extensive tooth loss. The All-on-4 concept allows for the immediate loading of prostheses onto the implants shortly after surgery. Compared to traditional implant approaches, All-on-4 reduces treatment time significantly. The concept utilizes tilted posterior implants, which take advantage of available bone and reduce the necessity for bone grafting in areas with insufficient bone volume. All-on-4 may be more cost-effective than traditional implant-supported restorations due to the reduced number of implants and the associated surgical procedures. The concept aims to provide a fixed, full-arch prosthesis that closely resembles natural teeth. Numerous studies have reported high success rates for the All-on-4 concept, with the majority of patients experiencing successful osseointegration and long-term stability of the implants. All-on-4 often results in a more comfortable experience for patients, with fewer surgical interventions and reduced healing periods. The tilted posterior implants increase the contact between bone and implant, enhancing stability and support for the prosthesis.